1990
DOI: 10.5820/aian.0403.1990.89
|View full text |Cite
|
Sign up to set email alerts
|

Much Remains to be Done

Abstract: The persistence of the traditional medical systems l among Canadian Native peoples has been fairly well documented, and some commentators have suggested that a resurgence in these systems is currently underway (Gregory, 1988). Although there have been very few studies of the utilization of these medical systems by contemporary Native peoples, there has been some suggestion that dual utilization is indeed practiced. Virtually nothing is known about the specific patterns of utilization, and the relationship, if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Second, low levels of contraceptive use combined with high levels of STDs (CDC, 1998) place AI female youths at high risk for exposure to HIV infection (Blum, Harmon, Harris, Bergeisen, & Resnick, 1992). Third, AIs have escalating rates of injection drug (ID) use (Conway et al, 1992; Gregory, 1992; Metler, Conway, & Stehr-Green, 1991) and are two to three times more likely than the general U.S. population to engage in excessive drinking (May, 1994; May & Moran, 1995), which often co-occurs with sexually risky behaviors (Brassard, Smeja, & Valverde, 1996; Walker et al, 1996). Urban AI samples have even higher rates of drinking than reservation-based samples (May, 1996).…”
Section: Risk Factors For Hiv Among Aismentioning
confidence: 99%
“…Second, low levels of contraceptive use combined with high levels of STDs (CDC, 1998) place AI female youths at high risk for exposure to HIV infection (Blum, Harmon, Harris, Bergeisen, & Resnick, 1992). Third, AIs have escalating rates of injection drug (ID) use (Conway et al, 1992; Gregory, 1992; Metler, Conway, & Stehr-Green, 1991) and are two to three times more likely than the general U.S. population to engage in excessive drinking (May, 1994; May & Moran, 1995), which often co-occurs with sexually risky behaviors (Brassard, Smeja, & Valverde, 1996; Walker et al, 1996). Urban AI samples have even higher rates of drinking than reservation-based samples (May, 1996).…”
Section: Risk Factors For Hiv Among Aismentioning
confidence: 99%
“…Milam & Ketcham (1983), for example, stated that a significant percentage of Native Americans lack the metabolic, hormonal, and neurological factors which permits the smooth metabolization of alcohol. In strong objection, however, May (1992) and others (Beauvais, 1992;Dorpat, 1992;Fleming, 1992;Gregory, 1992;Heath, 1992;Peters, 1992;Wolf, 1992) argued that, although there are some unique and specific differences, in general, Native Americans react to alcohol much like other people.…”
Section: Problem-drinking Among the Navajo Peoplementioning
confidence: 99%
“…It is also important to recognize that the majority of Native American drinkers, like most non-native people, enjoy alcohol socially without problems (Mail, 1992). Gregory (1992) also stated that although alcohol-related problems are indeed serious, the prevalence of Native American drinking is commonly exaggerated. Mail also reported that many Native American communities have reduced this trend significantly.…”
Section: Problem-drinking Among the Navajo Peoplementioning
confidence: 99%
“…PAV offered the consistent alternatives to chemical dependency and violence described by Gregory. 69 However, this program had not been formally evaluated. The revitalization of values and behaviors inherent in Indian culture that are reinforced by the PRIDE and PAV programs can be significant forces in rectifying social ills.…”
Section: Relevance To Researchmentioning
confidence: 99%